Kinds of Winter : Four Solo Journeys by Dogteam in Canada's Northwest Territories - Olesen, David (Book collections on Project MUSE., 2014)
"After a fifteen-year career as a sled dog racer, musher Dave Olesen turned his focus away from competition and set out to fulfill a lifelong dream. Over the course of four successive winters he steered his dogs and sled on long trips away from his remote Northwest Territories homestead, setting out in turn to the four cardinal compass points - south, east, north, and west - and home again to Hoarfrost River. His narrative ranges from the personal and poignant musings of a dogsled driver to loftier planes of introspection and contemplation. Olesen describes his journeys day by day, but this book is not merely an account of his travels. Neither is it yet another offering in the genre of wide-eyed southerner meets the Arctic, because Olesen is a firmly rooted northerner, having lived and travelled in the boreal outback for over thirty years. Olesen's life story colours his writing: educated immigrant, husband and father, professional dog musher, working bush pilot, and denizen of log cabins far off the grid. He and his dogs feel at home in country lying miles back of beyond. This book demolishes many of the cliches that imbue writings about bush life, the Canadian Far North, and dogsledding. It is a unique blend of armchair adventure, personal memoir, and thoughtful, down-to-earth reflection"--Publisher's description